Ultrasound image quality of the carpal tunnel during a pinch grip: effects of coupling media and wrist position - Denise Balogh; Michelle Campbell; Aaron M. Kociolek (Computer Methods in Biomechanics and Biomedical Engineering: Imaging & Visualization, 2024)
High quality ultrasound is required for evaluating carpal tunnel dynamics. The purpose of this study was to subjectively assess ultrasound video quality of the carpal tunnel with two commonly used coupling media (coupling gel, 7 mm standoff pad) in two wrist positions (0° neutral, 30° flexion) over the entire time course of a pinch grip. Seventeen participants completed a pinch grip while their carpal tunnel was scanned with ultrasound. The ultrasound videos were graded by two independent reviewers using 10-point scales encompassing median nerve detail, resolution, and total video quality. Intra- and inter-rater reliability were highest for median nerve detail (ICCs>.85). Ultrasound videos in the 0° neutral wrist condition resulted in significantly greater ratings of nerve detail compared to those in 30° wrist flexion. Future studies may benefit from a more customised approach to standoff pad thickness during dedicated analysis of the median nerve in a neutral wrist position.